2021
DOI: 10.3389/fpsyt.2021.755357
|View full text |Cite
|
Sign up to set email alerts
|

Financial Difficulties Correlate With Mental Health Among Bangladeshi Residents Amid COVID-19 Pandemic: Findings From a Cross-Sectional Survey

Abstract: Background: The COVID-19 pandemic is a global threat which has challenged mental resilience and impacted the psychological well-being of people across all age groups globally. The present study aimed to investigate how financial difficulties during the pandemic correlate with mental health among residents of Bangladesh.Methods: A cross-sectional survey was conducted on 4,020 residents from different parts of Bangladesh between July and September 2020, during a period of elevated risk of COVID-19 infection. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…This study revealed that except for anxiety and post-traumatic stress disorder symptoms, participants living in urban areas had a significantly lower risk of all psychological symptoms among vaccinated HCWs. These findings were in line with prior Bangladeshi studies ( 15 , 53 , 54 ), which claimed that HCWs working in urban areas had a higher rate of psychological outcomes. In a cross-sectional survey of 3,646 adults in Bangladesh, Avedin et al ( 55 ) discovered that 81% of urban participants wanted to be vaccinated.…”
Section: Discussionsupporting
confidence: 92%
“…This study revealed that except for anxiety and post-traumatic stress disorder symptoms, participants living in urban areas had a significantly lower risk of all psychological symptoms among vaccinated HCWs. These findings were in line with prior Bangladeshi studies ( 15 , 53 , 54 ), which claimed that HCWs working in urban areas had a higher rate of psychological outcomes. In a cross-sectional survey of 3,646 adults in Bangladesh, Avedin et al ( 55 ) discovered that 81% of urban participants wanted to be vaccinated.…”
Section: Discussionsupporting
confidence: 92%
“…Psychological stress is also experienced in people during COVID-19 periods, other than the stress from financial challenges, the career change intentions and pressures of a workforce reduction are putting shadows on the financial wellbeing ( Chen and Chen, 2021 ). The depression due to financial distress can lead to depression and ultimately to social problems of joblessness, divorce, living in a joint family, food scarcity, excessive sleep, and smoking ( Islam et al, 2021 ; Siddique et al, 2021 ).…”
Section: Thematic Analysismentioning
confidence: 99%
“…Conversely, adherence to physical distancing is affected by anxiety and the prospect of economic losses by unemployment [5]. Researches of mental health in community population during the COVID-19 have reported moderate level of stress [6,7], higher scores of depressive symptoms [6][7][8][9], anxiety [6][7][8][9], and symptoms of post-traumatic stress disorder [6]. Further, exposure of multiple waves of pandemic results in continual changes of risk perception, healthcare service use, and financial expenditure over time [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the mental health during the COVID-19 pandemic, associations were found between the perceived mental health status versus physical health [12], mental factors of health overconfidence [19], selfcompassion [20] and compassion from others [20], social factors of support from community [12,21] and anticipated deterioration in social cohesion and security [22]. In addition, demographic factors of age [9], sex (male [6] or female [7,9]), marital status (single [6,7] or divorced [6]), familial size [7], type [6] and strength [12] of religious beliefs are associated with perceived mental health status. Further, socioeconomic position of current unemployment [8,12], risks of unemployment [6,7], lower monthly household income [6,8,12], and risk of reduced income [7] are related to poor mental health.…”
Section: Introductionmentioning
confidence: 99%